The Market Price of Risk, Size of Market and Investor's Risk Aversion - Lintner, John (The Review of Economics and Statistics, 1970)
A PREVIOUS paper [9] developed a model of the structure of equilibrium prices for risk assets in a purely competitive in which a set of individually risk averse investors optimize their respective portfolios of risk assets in terms of common expectations and risk assessments with respect to a common horizon. When there is a riskless asset available for holding or borrowing at a fixed interest return and all probability assessments are normal (Gaussian) it was shown that in equilibrium a purely competitive will place an aggregate value on all the outstanding stock of any company V0j equal to the discounted value at the riskless rate r* of the certainty equivalent of -the distribution of its uncertain end-of-period aggregate value. This in turn is less than the statistical expectations V1* by the product of the market price of dollar